Consistent Timing of Arctic Permafrost Loss Across the CESM1 Large Ensemble. Issue 24 (15th December 2022) - McSweeney, Killian; Kooperman, Gabriel J.
Abstract: The Arctic is especially vulnerable to climate change and is warming faster than the global average. Changes in this region pose a heightened threat due to the immense amount of carbon frozen as organic material in the soil. When permafrost thaws, organic material decays and releases as greenhouse gases into the atmosphere, contributing to further warming. A better understanding of the processes that influence permafrost degradation is needed to inform climate adaptation and mitigation planning. This study assesses changes to Arctic permafrost across 35 ensemble member simulations from the Community Earth System Model 1 Large Ensemble Project, under the Representative Concentration Pathway 8.5 21st century scenario. Most Arctic near‐surface permafrost is lost by 2100, but timing varies across regions and with soil depth. Internal climate variability, represented by differences between ensemble members, has a constrained influence on degradation timing due to relative consistency of summer temperature increases and insulation by winter snow cover. Plain Language Summary: The Arctic contains a large amount of soil that stays frozen year‐round, called permafrost. As the Arctic warms in response to human caused climate change this soil is beginning to thaw, which has regional and global implications. Regionally, permafrost degradation can make the ground unstable, with potential to damage infrastructure such as roads, bridges, and structures. These frozen soils also contain a significant amount of organic material, which can breakdown and be released into the atmosphere as carbon dioxide and methane when the ground thaws. Globally, these greenhouse gases contribute to further warming and exacerbating climate change. Therefore, it is critical to understand how quickly the Arctic is warming and the processes that influence the timing of permafrost loss. In this study, we use a global Earth system model to explore the role of internal climate variability in influencing timing of permafrost thaw. We assess 35 simulations of the 21st century that differ only in their realization of variability. We find a steady decline in Arctic‐wide permafrost that is consistent in timing across the different simulations. Regionally, the thaw timing can vary up to ∼10 years, but is constrained by lower variability in summer surface temperatures and winter snow cover. Key Points: The timing of Arctic permafrost thaw in Community Earth System Model 1 Representative Concentration Pathway 8.5 experiments is dependent on latitude, elevation, soil depth, and internal variability Relatively consistent warming across ensemble members in summer limits the impact of internal variability on the timing of permafrost thaw Arctic‐wide permafrost loss has little variation across ensemble members, implying small differences in potential greenhouse gas emissions